فقه الحديث النبوي في بعض المسائل المتعلقة بالعبادات في وقت الأوبئة: The jurisprudence of the Prophet's hadith in some issues related to worship at the time of epidemics - Al-Boutibi , Youssef; An-Nadwi, Irwan santeri bin al-kawaid (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
ملخص البحث لقد واجه العالم في الآونة المستحدثة جائحة كورونا التي تهدد الأمة جمعاء، فتحير الناس بها ودهشوا، فأغلقوا الحدود والمتاجر والمساجد والمدارس وغيرها، وجاهدوا في مكافحتها، ومن جهودهم في ذلك بحثهم عن الدواء وطريقة العلاج، فهدي المسلمين سنة المصطفى ﷺ احتوت على إرشادات في مواجهة مثل هذه الأوبئة، فهذا البحث يروم الكشف عن ذلك الهدي وإبراز طرق التعامل معها وتحليل ما تضمنته النصوص النبوية من الأحكام إزاءه. وهو يتناول هذا البحث جملةً موضوع الأوبئة في ضوء الكتاب والسنة، ويعتمد على استقراء الأحاديث النبوية الخاصة بالأوبئة مع دراسة هذه الأحاديث سندًا وبيان حكمها إن كانت خارج الصحيحين. فيتم في هذا البحث بشكل عام الكشف على هدي السنة النبوية في التعامل مع الأوبئة مع ذكر صلتها بالمجتمع والعبادات، كما أن البحث يعالج ويحلل بعض النصوص المتعلقة بالنوازل الفقهية التي طرأت بسبب الأوبئة. وقد استخدمت في الدراسة المنهج الوصفي التحليلي، والمنهج الاستنباطي لمسائل الفقه، والمنهج النقدي الحديثي للوقوف على صحة الأحاديث. Abstract In recent times, the world has faced the Corona pandemic that threatens the entire nation, so people were confused and astonished by it, so they closed borders, shops, mosques, schools, etc., and struggled to combat it, and among their efforts in that was their search for medicine and a method of treatment, The guidance of Muslims is the Sunnah of the Chosen One, may God’s prayers and peace be upon him, which contains advice in confronting such epidemics. This research aims to reveal that guidance, highlight the ways to deal with it, and analyze the provisions of the prophetic texts about it. This research deals entirely with the subject of epidemics in the light of the Book and the Sunnah, and depends on extrapolating the hadiths of the Prophet regarding epidemics by studying these hadiths as a chain of transmission and clarifying their ruling if they are outside the Two Sahihs. In this research, in general, the guidance of the Prophet's Sunnah in dealing with epidemics is revealed, with a mention of its connection to society and worship. In this research, in general, the guidance of the Sunnah of the Prophet in dealing with epidemics is explained, with a mention of its relationship to society and worship. In this research, in general, the guidance of the Sunnah of the Prophet in dealing with epidemics is explained, with a mention of its relationship to society and worship. The research also deals with and analyzes some texts related to jurisprudential issues due to epidemics. The study used the descriptive analytical approach, the deductive approach to issues of jurisprudence, and the hadith critical approach to determine the authenticity of hadiths.